Implementation of strategic planning in the practice of modern medical institution management: methodological and applied aspects - Melnyk, Alla; Radzvyliuk, Leonid (Herald of Economics, 2021)
Introduction. Dismantling of the old economic model of health care as a purely budget organization, which took place under the influence of medical reform in Ukraine, led to a new nature of economic relations, the need for work and development of hospitals as participants in a competitive environment, regional or local health services market, exacerbated the impact of opportunities and threats. Given the uncertainty and dynamism of change, this highlights the need for strategic planning primarily at the level of medical institutions that provide secondary and tertiary (specialized) care to determine priorities and focus resources on achieving their development goals, which requires attention to the scientific and methodological framework ensuring this task.Purpose. The purpose of the article is to substantiate the need for strategic planning for the development of health care facilities in the context of medical reform and to develop recommendations for its implementation in their management.Research methods. In the course of the research the following methods were used: induction and deduction, system analysis - to determine the components of strategic planning at the level of health care, PEST analysis - to identify factors influencing the development of health care and factors that indicate the need to implement strategic planning in the hospital management system, institutional and comparative analysis - to identify features of strategic planning models, SWOT-analysis, expert assessments - to assess the internal and external environment of the organization, setting goals and strategic priorities.Results. Based on the analysis of the theoretical basis, the author’s approach to the interpretation of the essential characteristics of strategic planning of health care facilities is formed. The current state of the internal and external environment of health care facilities that provide secondary care in the context of health care reform in Ukraine is assessed, problems are identified. The planning system in medical institutions of this type is analyzed. The factors of actualization of the problem of implementation of strategic planning at the present stage are revealed and the necessity of its implementation in management of health care institutions is proved. Based on empirical evaluation conducted using the methods of expert collective commission, SPEIS-analysis, SWOT-analysis, the strengths and weaknesses of modern hospitals, opportunities and threats, the degree of probability and importance of the impact of opportunities and threats on the development of medical institutions, critical issues, the mission is specified, the main strategic goals and priorities are defined. An algorithm for the implementation of strategic planning in hospital management, a system of strategies and their content characteristics is proposed.Perspectives. Further research is needed on organizational design related to the implementation of strategies of medical institutions, organization of strategies, overcoming resistance to changes related to the implementation of strategies, training staff to work in new conditions, the use of other management actions aimed at building a perfect mechanism strategic planning.